From Freud's theories to brain function: integrating psychoanalysis and neurophysiology - Lima, Andréa Pereira de (2010)
BACKGROUND: Recent studies show that psychoanalytical and neuroscientific contributions to the understanding of human emotions and behavior can be complementary, and the interaction between these two approaches can be fruitful for both perspectives. OBJECTIVE: We revisited Freud's "structural model and encephalus", and propose and integrated reading of related psychoanalytical and neurobiological theories. METHOD: Bibliographic search and critical reflection about the selected papers. RESULTS: Considering Freud's classical descriptions, the id would be related to phylogenetically primitive neural circuits, such as the brain stem, the medial fasciculus of the forebrain (prosencephalon), medial amygdala, septum pellucidum, hypothalamus, nucleus accumbens, basal ganglia and thalamic nuclei. The superego, as a modulator of id's drive/motivations, would be represented mainly by the central nuclei of the amygdala and the insular cortex. The ego, as a mediator between the forces that operate between the id, the superego and the demands of external reality, would be related mainly to the prefrontal cortex, which is nowadays considered as one the underpinning of personality, given its importance to behaviors involving decision making and social adjustment. DISCUSSION: These preliminary notions illustrate the authors' point of view from an integrative reading of psychoanalysis and neuroscience.